REGULATORY OF FINANCIAL SUPPORT DIRECTIONS FOR TECHNOLOGICAL UPDATING OF PRODUCTION AND MODERNIZATION OF AGRICULTURAL ENTERPRISES’ ACTIVITY - Sas, L.S.; Matkovskyi , P.Ye. (The actual problems of regional economy development, 2019)
The objective of the article is to determine the directions of state financial support for innovative activity, in particular technological updating of production and modernization of agricultural enterprises" activity, stipulated by regulatory documents. During the research, the methods of analysis, systematization, grouping, abstraction were used in order to define regulatory documents on regulation of innovative activity of economic entities, isolation and consideration of directions of state financial support for technological updating of production and modernization of agricultural enterprises. Database of scientific research was made up of scientific works of domestic scientists-economists and legislative and normative documents on regulation of innovative activity and financial support for its implementation. The role and place of state financial support in ensuring technological updating of agricultural enterprises" production as a component of their innovative development are substantiated. The analysis of the regulatory support for the implementation of innovative activity is carried out. Directions of financial support for technological upgrading and modernization of agricultural enterprises were identified and considered, in particular as regards to budget support; creation of necessary conditions for financing; preferential lending; insurance of innovative activity; creation of specialized non-banking innovative financial institutions; preferential taxation; financial and economic support for technology transfer. The scientific novelty of the obtained results is to identify and reveal the directions of state financial support for technological updating of production and modernization of agricultural enterprises" activities. The results of the study can be used to organize the process of technological updating of production and modernization of agricultural enterprises.